Agriculture and the environment in the European Union: The pollution by nitrates - Izcara Palacios, Simón Pedro (Libros UAT, 2018)
During the last four decades, agriculture, both in Europe and in the group of more developed countries, has undergone a profound technological change, which has led to the concentration, specialization and intensification of agricultural activity. The ubiquity, scale and rapidity of the transformation of agrarian production methods, causing the immediate collapse of the traditional agrarian system, makes this process deserve the qualification of "agrarian revolution". This rapid modernizing process would not have been possible in the absence of a firm commitment, acquired by the different States, to: promote technological progress, facilitating the technical transformation of the agricultural sector; rationalize the agrarian structures, improving the productive efficiency of the farms, and protect their agriculture from foreign competition, creating an environment of economic security. Agriculture thus becomes the most regulated activity, from the point of view of production, and agrarian policies are a determining factor of agrarian development. In the European framework, by the middle of the century, agriculture was one of the most important economic sectors, both because of its contribution to employment and because of its economic significance. However, he suffered from notable deficiencies. The size of the agrarian structures was inadequate, it presented a clear technological delay in comparison with other more developed agricultures, like the North American one, the standards of life of the farmers and those of the urban population every time they widened more, to the detriment of the first ones, etc. On the other hand, in a climate of rapid urban-industrial development, an increase in agricultural production and productivity was necessary, which ensured the supply of food for a growing urban population and satisfied the labor needs of an expanding industrial sector. In a stage of rapid economic development, with ample employment opportunities for the agrarian population in the industrial sector, what seemed more logical was to improve the productive efficiency of those farms better sized economically, so that small farmers would be forced to abandon agrarian activity.